Effects of the COVID‐19 lockdowns on the management of coral restoration projects. Issue 8 (7th March 2022) - Montano, Simone; Dehnert, Inga; Seveso, Davide; Maggioni, Davide; Montalbetti, Enrico; Strona, Giovanni; Siena, Federica; Amir, Hana; Antoine, Athina; Marino‐Ramirez, Camila; Saponari, Luca; Shah, Nirmal J.; et al.
Abstract : Coral restoration initiatives are gaining significant momentum in a global effort to enhance the recovery of degraded coral reefs. However, the implementation and upkeep of coral nurseries are particularly demanding, so that unforeseen breaks in maintenance operations might jeopardize well‐established projects. In the last 2 years, the COVID‐19 pandemic has resulted in a temporary yet prolonged abandonment of several coral gardening infrastructures worldwide, including remote localities. Here we provide a first assessment of the potential impacts of monitoring and maintenance breakdown in a suite of coral restoration projects (based on floating rope nurseries) in Colombia, Seychelles, and Maldives. Our study comprises nine nurseries from six locations, hosting a total of 3, 554 fragments belonging to three coral genera, that were left unsupervised for a period spanning from 29 to 61 weeks. Floating nursery structures experienced various levels of damage, and total fragment survival spanned from 40 to 95% among projects, with Pocillopora showing the highest survival rate in all locations present. Overall, our study shows that, under certain conditions, abandoned coral nurseries can remain functional for several months without suffering critical failure from biofouling and hydrodynamism. Still, even where gardening infrastructures were only marginally affected, the unavoidable interruptions in data collection have slowed down ongoing project progress, diminishing previous investments and reducing future funding opportunities. These results highlight the need to increase the resilience and self‐sufficiency of coral restoration projects, so that the next global lockdown will not further shrink the increasing efforts to prevent coral reefs from disappearing.